What the Joint Commission Medication Management Titration Standards Mean to Quality Care for Complex Patients. Issue 1 (January 2023) - Chechel, Laura; McLean, Barbara; Slazinski, Theresa; Rincon, Teresa
Abstract: The Joint Commission (TJC), the nation's largest healthcare accreditor, was founded in the 1950s. Its Standards for Medication Management (MM) of titratable medications focused on prescriptive ordering practices versus reliance on nurse clinical decision making. The use of measurable endpoints to guide nurse decision making regarding medication titration has been the standard of care since the inception of TJC. Evidence to support altering these practice patterns is lacking. Using the 6 aims for the healthcare system (safe, timely, effective, efficient, equitable, and patient-centered) from the National Academy of Medicine, formerly the Institute of Medicine, and the American Association of Critical-Care Nurses Healthy Work Environment essential standards (skilled communication, true collaboration, effective decision making, appropriate staffing, meaningful recognition, authentic leadership), this article examines the impact of TJC MM standards on system design in critical care environments.